Formation of requirements for building objects throughout their full life cycle - Kovalov, V.; Kravchunovska, T.; Danylova, T.; Yepifantseva, S. (Ways to Improve Construction Efficiency, 2019)
The main requirements for building projects during their life cycle – design, construction, maintenance – for the further formation and formalization of determining factors and quantifying their impact on the cost and duration of construction, predicting the best values of technical and economic indicators of projects, taking into account the effective use resources, energy efficiency, environmental safety and values of urban areas.